2016
DOI: 10.1007/s12185-016-2071-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes from imatinib mesylate to second generation tyrosine kinase inhibitors improve renal impairment with imatinib mesylate in chronic myelogenous leukemia

Abstract: Understanding adverse events in long-term tyrosine kinase inhibitor (TKI) therapy for chronic myelogenous leukemia (CML) is important. We investigated changes in renal function during TKI therapy for CML. We retrospectively analyzed levels of serum creatinine (sCrn) and values of estimated glomerular filtration rate (eGFR) from June 2001 to March 2015. Sixty patients initially treated with imatinib were enrolled in this study. Continuous variables of sCrn and eGFR were compared by paired student's t test. Medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The literature search identified a total of 684 studies, and 677 articles were screened based on title and abstracts screening in the first screening after removing duplicates, and 25 articles were screened in the full-text screening phase. Finally, only nine articles [10][11][12][16][17][18][19][20][21] were qualified for inclusion in this study (Figure 1). A list of articles not eligible for inclusion in the full-text screening phase is presented with a reason for exclusion in Supplementary file S3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search identified a total of 684 studies, and 677 articles were screened based on title and abstracts screening in the first screening after removing duplicates, and 25 articles were screened in the full-text screening phase. Finally, only nine articles [10][11][12][16][17][18][19][20][21] were qualified for inclusion in this study (Figure 1). A list of articles not eligible for inclusion in the full-text screening phase is presented with a reason for exclusion in Supplementary file S3.…”
Section: Resultsmentioning
confidence: 99%
“…9 Despite the acceptable long-term safety profile, recently, multiple epidemiological studies have linked imatinib with the alteration of kidney function characterized by a decline in estimated glomerular filtration rate (eGFR). [10][11][12] Hino et al conducted a retrospective cohort study in 60 CML patients and found significant deterioration in eGFR and serum creatinine levels after only 1 year of treatment. 10 A retrospective study from the United States (US), based on 259 newly diagnosed CML patients, concluded that imatinib might increase the risk of renal function decline in patients with pre-existing renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Clinicians have recently reported that transitioning from imatinib mesylate to second-generation tyrosine-kinase inhibitors after incidence of renal injury controls disease progression as well as allows recovery of renal impairment; however, all these cases were in the CML population. [30] Current practice guidelines for imatinib therapy in the treatment of CML recommend monitoring creatinine and making dose adjustments to avoid long-term toxicity. Our case highlights the employment of the same principle in the management of GIST and presents renal toxicity as a cause of concern in imatinib safety and tolerance.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Previous studies have reported that CML patients suffered chronic renal injury in long-term imatinib therapy, which could be reversed when patients switching to nilotinib therapy from imatinib (4)(5)(6). In this report, we describe a patient with CML, rst treated with imatinib, then switched to nilotinib due to resistance.…”
Section: Introductionmentioning
confidence: 99%